The isolation, enumeration, and characterization of Rhizobium bacteria of the soil in Wamena Biological Garden (Biodiversitas Journal of Biological Diversity, 2016)
The eleven soil samples have been isolated and characterized. The aims of the study were to get the pure culture and some data which described about enumeration and especially their characters in relation to the acids and bases reaction in their growth. The isolation of the bacteria use Yeast Extract Mannitol Agar medium (YEMA) while the characterization by using YEMA medium mixed with Brom Thymol Blue and Congo Red indicators respectively. The results showed that eighteen isolates have been isolated which consisted of three low growing and fifteen fast growing bacteria. Two isolates were not indicated Rhizobium and sixteen were Rhizobium. Density of Rhizobiumenumeration was varied which related to soil organic matter content. The enumeration bacteria in YEMA medium were in the range of 0.6 x 105 and 11.6 x 105 CFU /g soil. The highest population was found in soil sample of Wieb vegetation.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: Rhizobium, Wamena Biological Garden, isolation, enumeration, characterization.